El maltrato psicológico infantil y su influencia en el comportamiento de los niños y niñas del cuarto año de Educación Básica de la Unidad Educativa "Digna Beatriz Cerda Neto" del cantón Pujilí durante el año lectivo 2016-2017 - Estrada Venegas, Viviana Elizabeth (2018)
Psychological abuse is any action that produces mental damage in the short, medium and long term for that reason it is believed appropriate to help them, through talks with parents, to find possible solutions to improve behavior, the project is carried out in the Educational Unit "Digna Beatriz Cerda Neto" of the Puembo campus, Pujilí canton, Cotopaxi province. The purpose is to take into account that children are beings that need to be protected physically, emotionally and psychologically; Negative words can cause serious disturbances that will last the rest of their lives. Field research was used within the educational and bibliographic establishment because its theoretical contextualization requires the criterion of different authors. As a contribution allowed to strengthen the behavior of children, the direct beneficiaries were the students of the morning section who will have a cognitive development according to their needs of academic training. The impact it aims to achieve is to strengthen the knowledge of the teacher, raise awareness about the negative influence that child psychological abuse has on the behavior of children. This project is very important because it allows us to solve a problem that affects the institution and has the support of authorities, teachers, parents and students who are interested in the development and application. The theoretical contribution of this project guides the practice to become aware of the influence of psychological abuse on students in this way to improve the behavior of children who will have a cognitive development according to their needs in academic education.